Implementasi Dashboard Real-Time Untuk Memantau Proses Pendaftaran Webinar Berbasis Website - Adji Prasetyo; Zuhri Halim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research aims to develop a web-based information system with an analytical dashboard to improve business process efficiency and campaign evaluation. The research method employs the Waterfall model. The system is developed with a centralized database and is equipped with a data visualization dashboard using Microsoft Power BI, divided into Revenue and Activity pages. The implementation results in a functional website for webinar registration integrated with the database. Alpha and beta testing shows that the system operates according to expected functionality, has an easy-to-understand interface, and assists the registration and monitoring processes. Based on data from 20 user respondents, this registration website system has successfully achieved a very high level of acceptance and satisfaction. An overwhelming majority of respondents (90% to 100%) rated the website as responsive, fast, very helpful, easy to understand, and providing a good impression. Although there is slight room for improvement in operational ease (with 35% stating it is not difficult, while the remainder were possibly neutral or disagreed), the overall survey results prove that this system functions very effectively as a decision-support tool for management, as well as a successful and positive medium for interaction with prospective registrants. It is concluded that this system has successfully become an effective decision-support tool for management through periodic reporting.